Characterising the outcomes, impacts and implementation challenges of advanced clinical practice roles in the UK: a scoping review. Issue 8 (5th August 2021) - Evans, Catrin; Poku, Brenda; Pearce, Ruth; Eldridge, Jeanette; Hendrick, Paul; Knaggs, Roger; Blake, Holly; Yogeswaran, Gowsika; McLuskey, John; Tomczak, Philippa; Thow, Ruaridh; Harris, Peter; et al.
Abstract : Objectives: In response to demographic and health system pressures, the development of non-medical advanced clinical practice (ACP) roles is a key component of National Health Service workforce transformation policy in the UK. This review was undertaken to establish a baseline of evidence on ACP roles and their outcomes, impacts and implementation challenges across the UK. Design: A scoping review was undertaken following JBI methodological guidance. Methods: 13 online databases (Medline, CINAHL, ASSIA, Embase, HMIC, AMED, Amber, OT seeker, PsycINFO, PEDro, SportDiscus, Osteopathic Research and PenNutrition) and grey literature sources were searched from 2005 to 2020. Data extraction, charting and summary was guided by the PEPPA-Plus framework. The review was undertaken by a multi-professional team that included an expert lay representative. Results: 191 papers met the inclusion criteria (any type of UK evidence, any sector/setting and any profession meeting the Health Education England definition of ACP). Most papers were small-scale descriptive studies, service evaluations or audits. The papers reported mainly on clinical aspects of the ACP role. Most papers related to nursing, pharmacy, physiotherapy and radiography roles and these were referred to by a plethora of different titles. ACP roles were reported to be achieving beneficial impacts across a range of clinical and health system outcomes. They were highly acceptable to patients and staff. No significant adverse events were reported. There was a lack of cost-effectiveness evidence. Implementation challenges included a lack of role clarity and an ambivalent role identity, lack of mentorship, lack of continuing professional development and an unclear career pathway. Conclusion: This review suggests a need for educational and role standardisation and a supported career pathway for advanced clinical practitioners (ACPs) in the UK. Future research should: (i) adopt more robust study designs, (ii) investigate the full scope of the ACP role and (iii) include a wider range of professions and sectors.